Patronage Factors of Motor Vehicle Takaful in Kano State, Nigeria - Alhassan Yahaya; Sagir Muhammad Sulaiman; Habu Abdu Aminu (Universitas Muhammadiyah Yogyakarta, 2022)
The Nigerian insurance industry has been associated with low patronage, thus contributing less than 1% to the Gross Domestic Product (GDP). The marketing and distribution segment of the Nigerian oil and Gas industry is facing multiple challenges including difficulty in transporting product through pipelines which necessitate the use of alternative means of transportation by road (Trucks). The main objective of this study is to empirically examine the determinants of patronage of motor vehicle Takaful by members of National Association of Road Transport Owners (NARTO-PTD) Kano State. The population of the study is 320 registered members of NARTO-PTD. Using Taro Yamane sample size formula, the study arrives at a sample of 178 respondents who were selected using simple Random Sampling Techniques. Partial Least Square - Structural Equation Modelling (PLS-SEM) method was employed to test the hypotheses of the study. The result reveals that while awareness is insignificant but perception and religiosity significantly affect patronage of motor vehicle takaful by members of NARTO-PTD in Kano State. The study recommends Takaful Companies to develop policies that will further encourage those highly religious and attract those that are not highly religious through organizing educative programs in masjids and other religious avenues and places of worship. Lastly, the study recommends developing policies that will strengthening the perception (NARTO-PTD) members toward Takaful.